UJI PENGGUNAAN ETHREL DAN PUPUK NPK TERHADAP PRODUKSI MELON (Cucumis Melo. L) - Shinta Sari; T Rosmawaty; Hercules Gultom (UIR Press, 2012)
The aim of this research was to know the effect of ethrel and NPK fertilizer application interactionally and individually on production of Melon. The research used completely randomized design which consisted of 2 factors. The R factor (using ethrel) consisted of 4 levels and N (using NPK fertilizer) was also 4 levels with three replications and the total was 48 plots. The observated parameters were flowering age, harvested age, circle fruit, fruit weight, production per plot, and fruit taste quality. The observation data for each treatment was analyzed statistically and was done advanced different test with 5% significant level. Interactionally, the ethrel and NPK applications had only a significant effect on circle fruit with the best treatment of R2N1 (ethrel concentration of 5 cc/l and NPK of 10 g/plant). The ethrel application had only a significant effect on flowering age, harvested age, and fruit weight with the best treatment of R2 (5 cc/l). NPK application only affected significantly on flowering age and fruit weight with the best treatment of N1 (10 g/plant).